(untitled) - Chappell, Eric (Indianapolis, 2013)
Get a thorough introduction to AutoCAD Civil 3D, the industry-leading engineering software used to design roads, highways, subdivisions, drainage and sewer systems, and more. This Autodesk Official Press book is a unique learning resource that features concise, straightforward explanations and real-world, hands-on exercises and tutorials. With compelling full-color screenshots and approachable exercises that demonstrate core features and functions, the book helps you gain understanding and confidence as you master this premiere civil engineering software.
Keywords: Image processing,Xử lý ảnh; Computer programs,Chương trình máy tính